Malaysia and the issue of human trafficking: Root causes, securitisation and responses / Sheila Devi Michael - Sheila Devi, Michael (2016)
Human trafficking is a grave transnational organised crime which has been outstandingly on the rise for the past two decades. With increasing global and security concern, human trafficking has stirred up many actors at international as well as at state level to play vital role in curbing this crime. The research on the events of human trafficking in Malaysia through the efforts to combat this crime in the country by state and non-state actors is significant for national interest, to protect the sovereignty of the country and the human rights of the people who fall easily as victims into the hands of ruthless traffickers. Malaysia is identified as a country of origin besides a lucrative destination and transit point for traffickers to transport their victims. Concurrently, internal trafficking also occurs in Malaysia. Human trafficking is reported to be the second profitable business after drug cartel. It is an illicit clandestine movement and the nature of this crime imposes numerous security challenges to a state and its people. The security of the people is poignant and human security is the vital core of humanity by enhancing human freedom and human fulfilment. Human trafficking violates the freedom of a person and it is against human rights. The essential question is if the Malaysian government doing enough in curbing human trafficking in the country? The Malaysian government in collaboration with its agencies have responded by outlining a National Action Plan against Trafficking in Persons (2010- 2015) as a preventive measure. With numerous efforts to combat human trafficking, perpetrators are still motivated by the high profits from this lucrative business of trafficking people. The push and pull factors are determinants for such an illegal activity to operate in Malaysia and globally. People become a prey easily due to circumstances and many are trafficked without their knowledge as human trafficking has many forms and the modus operandi vary from countries and destinations. Subsequently, it has negative impact on the socio-economics and politics of a country. Therefore, creating awareness through education system, media and social networks may prevent men, women and children from involving in situations that may lead to human trafficking and eventually becoming a victim.